2021
DOI: 10.1016/j.mmcr.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

First case of Kluyveromyces marxianus (Candida kefyr) late onset keratitis after lamellar endothelial corneal graft

Abstract: We present a case of Kluyveromyces marxianus keratitis nine months after Descement's membrane endothelial keratoplasty (DMEK) in a patient with Fuchs endothelial disease. Endothelial scraping revealed this rare yeast infection at the interface between graft and host cornea. Immediate antifungal treatment with intracameral and corneal intrastromal injections of voriconazole and amphotericin B remained unsuccessful, requiring penetrating keratoplasty. This case highlights the challenging m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Several studies reported opportunistic infections with K. marxianus in humans with various predisposing conditions but could not be appropriately evaluated due to uncertainties regarding methodology for species identification (Nurdin et al, 2021;Alp et al, 2021;Pedaci et al, 2021;Jyothi et al, 2021). Aldejohann et al (2021) reported eye infection with K. marxianus following surgery (transplantation of a lamellar endothelial corneal graft). In a literature review, Bayoumi et al ( 2021) found that K. marxianus was one of several yeasts that had been reported to cause gut fermentation syndrome (GFS), where consumed carbohydrates are converted to alcohol by the gut microbiota.…”
Section: Kluyveromyces Marxianusmentioning
confidence: 99%
“…Several studies reported opportunistic infections with K. marxianus in humans with various predisposing conditions but could not be appropriately evaluated due to uncertainties regarding methodology for species identification (Nurdin et al, 2021;Alp et al, 2021;Pedaci et al, 2021;Jyothi et al, 2021). Aldejohann et al (2021) reported eye infection with K. marxianus following surgery (transplantation of a lamellar endothelial corneal graft). In a literature review, Bayoumi et al ( 2021) found that K. marxianus was one of several yeasts that had been reported to cause gut fermentation syndrome (GFS), where consumed carbohydrates are converted to alcohol by the gut microbiota.…”
Section: Kluyveromyces Marxianusmentioning
confidence: 99%
“…Ocasionalmente esta especie se reporta en candidiasis superficial 7 o keratitis 8 . Otros autores han reportado la presencia de esta levadura en infección pulmonar en paciente transplantado cardíaco 9 , en esofagitis en un paciente con carcinoma de orofaringe 10 , en quiste ovárico 11 y en infección pulmonar mixta con Aspergillus flavus en un paciente con leucemia 12 .…”
unclassified